A forensic investigation of the Xiaoshan ramp bridge collapse. (1st December 2020) - Peng, Weibing; Tang, Zhiwen; Wang, Dongze; Cao, Xinjian; Dai, Fei; Taciroglu, Ertugrul
Highlights: This bridge collapse analysis exploited evidence contained in wreckage photos. Visual analysis revealed the collapse rooting from design modification. Design modification resulted in severe compression of the western pedestals. Small earthquake then caused transverse movement and thereby collapse of the bridge. Abstract: A ramp bridge in Hangzhou of Zhejiang Province in China collapsed on April 14, 2017. This paper presented a forensic analysis of the collapse that combines bridge metadata, witness accounts, video footages that captured the event, and numerical simulations. The forensic case study showed that the replacement of the originally symmetric section of the curved ramp bridge's box girder with an asymmetric one together with the introduction of a sidewalk on its outer side led to excessive forces on the lateral supports. Construction deviations from the intended configurations of the padstones further exacerbated the situation. A relatively minor nearby earthquake (4.2 Richter magnitude) then caused the already-precarious superstructure to slip westwards by approximately 10 cm and induced highly localized compression damage to the padstones. A sliding surface was thus formed through successive crushing of several padstones, which led to the collapse of the bridge. The present case study shows that a proper fusion of pre- and post-event data can shed light on the overturning collapse mechanisms of box-girder bridges, and illuminates potential hazards in existing bridges with similar geometries.